RELEVANSI PEMIKIRAN FRIEDRICH WILHELM AUGUST FROEBEL DI TAMAN KANAK-KANAK AISYIYAH BUSTANUL ATHFAL (ABA) DI YOGYAKARTA TAHUN 1919-1932 - Dimas Aldi Pangestu; Naufal Raffi Arrazaq (Universitas Negeri Gorontalo, 2026)
Froebel Kindergarten reaches the Dutch East Indies colony with the establishment of Kindergarten such as Froebel Kindergarten Aisyiyah. This study aims to explain the educational thoughts of Friedrich Wilhelm August Froebel, describe the concept of learning in ABA Kindergarten in 1919-1932, and analyze the relevance of Friedrich Wilhelm August Froebel's educational thoughts in ABA Kindergarten Yogyakarta in 1919-1932. The research method uses the historical method, which consists of four stages: heuristics, source verification, interpretation, and historiography. The results of this study are 1) Froebel's educational concept in early childhood has principles such as independent activity, gift, occupation, social and theological participation; 2) ABA Kindergarten has a learning concept that is liberating, active and based on Islamic religion. The learning methods in ABA Kindergarten at that time were storytelling method, question and answer method, field visit method, demonstration method, sociodrama method, project method, experimental method, assignment method, drawing method, listening method, playing method, counting method, writing method and arithmetic method; 3) ABA Kindergarten has a learning method with Frobelian principles. Students are given freedom in learning, guided according to their developmental stages through appropriate methods, and given a theological foundation through moral learning based on Islamic religion. The game concept applied in Yogyakarta Kindergarten is instructivist in nature where children will follow instructions or directions from educators and then imitate them. The aspects developed in the learning process are mind, matter and immanent.